HIDAYATUL MUTA'ALLIM AS THE MAIN FOUNDATION OF THE FORMATION OF MODERATE ISLAMIC CHARACTER FOR STUDENTS - Sinta, Dewi; Rosidi, Ahmad; Rohman, Fathor; Jali, Hasan (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2023)
The formation of the character of moderate Islamic students was a big responsibility of the asatidz or teachers in the country in building the younger generation. This research used research methodology with a qualitative approach with the type of case study research conducted at the Al-Qodiri Islamic Boarding School, especially in Madrasah Tsanawiyah "Unggulan" Al-Qodiri with the aim of analyzing the use of the book Hidayatul Muta'allim as a basic guideline for the formation of moderate Islamic character of grade VII MTs "Unggulan" Al-Qodiri students. The results showed that the book Hidayatul Muta'allim is very relevant as the main foundation for the formation of moderate Islamic character Santri in Madrasah Tsanawiyah "Unggulan" Al-Qodiri Jember. The implications of this research were expected to facilitate the moderate Islamic character of students.